2012
DOI: 10.1063/1.4742342
|View full text |Cite
|
Sign up to set email alerts
|

High-spin organic molecules with dominant spin-orbit contribution and unprecedentedly large magnetic anisotropy

Abstract: High-spin organic molecules with dominant spin-orbit contribution to magnetic anisotropy are reported. Quintet 4-azido-3,5-dibromopyridyl-2,6-dinitrene (Q-1), quintet 2-azido-3,5-dibromopyridyl-4,6-dinitrene (Q-2), and septet 3,5-dibromopyridyl-2,4,6-trinitrene (S-1) were generated in solid argon matrices by ultraviolet irradiation of 2,4,6-triazido-3,5-dibromopyridine. The zero-field splitting (ZFS) parameters, derived from electron spin resonance spectra, show unprecedentedly large magnitudes of the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 45 publications
(29 reference statements)
3
36
0
Order By: Relevance
“… The contribution of the spin‐orbit (SO) coupling to parameter D is one order of magnitude greater than the contribution of the spin–spin (SS) interaction. The main SO contribution is the SOMO→SOMO spin‐flip interaction between excited singlet and ground triplet states (Table S3). The PBE/Ahlrichs‐DZ level of theory is universal and describes the experimental results for all known triplet phosphinidenes (Table ), as well as for high‐spin nitrenes The calculated components ( A x and A y ) of hyperfine structure tensor A are similar to those obtained from the experimental spectrum, see Table . …”
Section: Methodssupporting
confidence: 56%
See 2 more Smart Citations
“… The contribution of the spin‐orbit (SO) coupling to parameter D is one order of magnitude greater than the contribution of the spin–spin (SS) interaction. The main SO contribution is the SOMO→SOMO spin‐flip interaction between excited singlet and ground triplet states (Table S3). The PBE/Ahlrichs‐DZ level of theory is universal and describes the experimental results for all known triplet phosphinidenes (Table ), as well as for high‐spin nitrenes The calculated components ( A x and A y ) of hyperfine structure tensor A are similar to those obtained from the experimental spectrum, see Table . …”
Section: Methodssupporting
confidence: 56%
“…Our interest in the EPR spectra of organic phosphinidenes was motivated by the study of the heavy‐atom effect on magnetic anisotropy as a continuation of our previous studies . Our initial EPR measurements in photolyzed frozen solutions with precursors 1 a and 1 b showed that the spectrum of photolytic product 2 (Scheme ) is significantly different from that reported in Ref.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…The halonitrenes FN, ClN, and BrN have the highest D values (2.46, 3.4, and ca. 17 cm −1 , respectively), as a result of large contributions of SOC. Alkoxynitrenes, R−O−N, also have very high D values (ca.…”
Section: Triplet Nitrenes and Carbenes Spin Densities And Mixing Ofmentioning
confidence: 71%
“…[50,78] Theh alonitrenes FN, ClN,a nd BrN have the highest D values (2.46, 3.4, and ca. 17 cm À1 ,r espectively), [79,80] as ar esult of large contributions of SOC.Alkoxynitrenes,R À O À N, also have very high D values (ca. 1.96 cm À1 ) [81] that are about 30 %h igher than predicted from the natural spin densities,t hereby implying significant contribution from SOC.T his finding can be explained by mixing of the triplet state with the zwitterionic singlet RO + =N À .I ng eneral, as erious deviation from the straight line hints at ap ossible importance of SOC.T he E values are also dependent on SOC.…”
Section: Triplet Nitrenes and Carbenes Spin Densities And Mixing Ofmentioning
confidence: 99%